Model Matematika Kecanduan Media Sosial Tiktok Pada Siswa: Sebuah Kajian Dengan Pendekatan SEI1I2I3R - Abdul Aziz; Luthfia Azzahra; Selvia Lovita Sari; Adib Mustofa Zaman; Wayan Rumite (FKIP Universitas Mataram, 2024)
TikTok addiction among high school students in Lampung Province is very worrying. This study aims to identify and understand the spread model of TikTok addiction as well as analyze the equilibrium stability of the model. The subjects of this research are high school students in Lampung Province. The research sample consists of 90 students, with details of 63 females and 27 males, who were randomly selected from the population of high school students in Lampung Province. The first step is to build a mathematical model based on assumptions related to the models, as well as the characteristics of addiction. From this, diagrams and mathematical models in differential equations are formed. Next, the researcher will calculate the basic reproductive value and determine the addiction-free and endemic equilibrium points based on a pre-built model. The next stage is to analyze the stability of these equilibrium points. Ultimately, the simulation will be carried out using the model program by entering the initial values and parameters set. Based on the research results, a building model of Tiktopk addiction was obtained, namely , , , , , , with . Based on the results of the analysis, it was found that the basic reproductive number () of social media addiction among students reached 1.02. This indicates that, on average, one student who is already addicted can spread his addiction to one to two other vulnerable students in the sample population studied. The number of students in each compartment initially has an upward graph, gradually decreasing over time, and is in equilibrium. Based on the study's results, it was found that the equilibrium points of the differential equation describing the mathematical model are stable.